On the multidimensional central limit theorem - Paulauskas, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Паулаускас. О многомерной центральной предельной теореме V. Paulauskas. Apie daugiamatę centrinę ribinę teoremą